2002
DOI: 10.3201/eid0809.010524
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Impact of Reemergence of Rabies, New York

Abstract: This report summarizes the spread of a raccoon rabies epizootic into New York in the 1990s, the species of animals affected, and human postexposure treatments (PET). A total of 57,008 specimens were submitted to the state laboratory from 1993 to 1998; 8,858 (16%) animals were confirmed rabid, with raccoons the most common species (75%). After exposure to 11,769 animals, 18,238 (45%) persons received PET, mostly because of contact with saliva or nervous tissue. We analyzed expenditure reports to estimate the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 20 publications
1
46
0
3
Order By: Relevance
“…This highlights the critical prevention message of having cats vaccinated and of avoiding stray cat exposure, to eliminate the risk of rabies as well as the expense associated with testing and postexposure prophylaxis. The costs associated with preventing rabies are substantial Chang et al, 2002;Shwiff et al, 2007). Raccoon rabies spread across Massachusetts from two distinct foci of introduction in 1992, one in the northcentral part of the state and one in the extreme southwestern corner, as shown in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the critical prevention message of having cats vaccinated and of avoiding stray cat exposure, to eliminate the risk of rabies as well as the expense associated with testing and postexposure prophylaxis. The costs associated with preventing rabies are substantial Chang et al, 2002;Shwiff et al, 2007). Raccoon rabies spread across Massachusetts from two distinct foci of introduction in 1992, one in the northcentral part of the state and one in the extreme southwestern corner, as shown in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the potential local and regional costs of rabiescaused expenses within the US have been published (i.e., Uhaa et al, 1992;Kriendel et al, 1998;Chang et al, 2002; Shwiff et al, submitted for publication). Most of these have focused on direct and indirect medical expenses.…”
Section: Empirical Estimates Of Rabies Costsmentioning
confidence: 99%
“…Several studies have shown that memory response to a booster dose may be induced years after primary immunization, even among those whose antibody titres fell below the 0.5 IU/ml threshold considered protective (26,27). Malerczyk et al reported an anamnestic response to a booster dose in individuals vaccinated 15 years earlier (25) and other studies report an anamnestic response to a booster dose to up to 21 years after primary immunization (6).…”
Section: Interval Between the Third Dose And The Serological Test (Wementioning
confidence: 94%
“…In recent years, the emergence of rabies was observed in southern Quebec with the migration of a new strain of raccoon rabies from the United States (27,28). Participants in this study were veterinary students working in an enzootic area.…”
Section: Interval Between the Third Dose And The Serological Test (Wementioning
confidence: 99%